Identification and analysis of microRNAs responsive to abscisic acid and methyl jasmonate treatments in Persicaria minor - Abdul Fatah A. Samad,; Nazaruddin, Nazaruddin; Jaeyres Jani, Jaeyres; Ismanizan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Persicaria minor has been recognised as a plant with high content of volatile organic compounds (VOC) especially terpenoid and green leaf volatile (GLV). Previous finding had showed signaling molecules such as abscisic acid (ABA) and methyl jasmonate (MeJA) can increase the VOC content in plant. In this study, we performed next generation sequencing (NGS) of small RNA to uncover miRNAs roles and their response to both phytohormones (ABA and MeJA) in P. minor. For both ABA and MeJA treated P. minor, small RNA libraries containing 17,253,566 and 40,437,576 reads were generated, respectively. In addition, 18,634,904 reads were generated in plant treated with sterile distilled water which served as control. In these libraries, a total of 88 miRNAs were identified, comprising 41 known and 47 novel miRNAs. It was observed that 21 and 38 miRNAs were significantly regulated in ABA and MeJA libraries, respectively. Four selected miRNAs related to VOC pathways were subjected to RT-qPCR analysis and found to display diverse expression patterns with their targets. This study provides the initial framework for further exploration of miRNA roles in ABA and MeJA responses.